Healthcare interpreter utilisation: analysis of health administrative data - Nicole Blay; Sharelle Ioannou; Marika Seremetkoska; Jenny Morris; Gael Holters; Verily Thomas; Everett Bronwyn (BMC, 2018)
Abstract Background Few people with limited English proficiency are provided with the services of a healthcare interpreter when admitted to hospital. This retrospective study utilised health administrative data to explore which patients with limited English proficiency were provided with a healthcare interpreter during their hospital admission. Method A retrospective analysis of health administrative data for adult overnight-stay patients admitted to a public hospital in a region of significant cultural and linguistic diversity in Sydney, Australia in 2014-2015. Descriptive analyses were used to explore demographic and diagnostic data. Chi-square and analysis of variance were used to test for association between variables. Results The site hospital provided for 19,627 overnight-stay episodes of care over the one year period. Emergency admissions made up 70.5% (n = 13,845) of all hospital admissions and obstetric patients 11.7% (n = 2291). For 15.7% (n = 3074) of episodes of care a healthcare interpreter was identified at hospital admission as being required. In 3.7% (n = 727) of episodes of care a healthcare interpreter was provided. Patients who received an interpreter were more likely to be female, of a younger age and admitted to hospital for childbirth. Conclusions A minority of patients with limited English proficiency received a healthcare interpreter during their episode of care. The majority of interpreter services were provided to obstetric patients.